ADVANCEMENTS IN SOLAR TECHNOLOGY: DUAL AXIS SOLAR TRACKING SYSTEMS - X. Mamajonov ,; I.M.Madaminov , (TADQIQOTLAR.UZ, 2024)
Abstract: The article explores the innovative field of Dual Axis Solar Tracking Systems, which enhances the efficiency of solar energy capture by precisely aligning solar panels with the sun's movements in both horizontal and vertical axes. The principles, advantages, challenges, and potential applications of these tracking systems are examined. Highlighting increased energy output, improved efficiency, and versatility as key advantages, the article acknowledges challenges such as cost, maintenance, and space requirements. With potential applications ranging from residential to remote off-grid areas, Dual Axis Solar Tracking Systems represent a promising advancement in the quest for cleaner and more sustainable energy solutions.